Usefulness of Home Screening for Promoting Awareness of Impaired Glycemic Status and Utilization of Primary Care in a Low Socio-Economic Setting: A Follow-Up Study in Reunion Island - Adrian Fianu; Éric Doussiet; Nadège Naty; Sylvaine Porcherat; Corinne Mussard; Karim Boussaïd; Muriel Cogne; Patrick Gérardin; François Favier (Kerman University of Medical Sciences, 2022)
Background  Low socio-economic settings are characterized by high prevalence of diabetes and difficulty in accessing healthcare. In these contexts, proximity health services could improve healthcare access for diabetes prevention. Our primary objective was to evaluate the usefulness of home screening for promoting awareness of impaired glycemic status and utilization of primary care among adults aged 18-79 in a low socio-economic setting. Methods  This follow-up study was conducted in 2015-2016 in Reunion Island, a French overseas department in the Indian Ocean. Enrollment and screening occurred on the same day at the home of participants (N = 907). Impaired glycemic status was defined as [glycated hemoglobin (HbA1c) ≥5.7%] OR [fasting capillary blood glucose (FCBG) ≥1.10 g/L] OR [HbA1c = 5.5-5.6% and FCBG = 1.00-1.09 g/L]. Medical, socio-cultural, and socio-economic characteristics were collected via a face- to-face questionnaire. A one-month telephone follow-up survey was conducted to determine whether participants had consulted a general practitioner (GP) for confirmation of screening results. A multinomial polytomous logistic regression model was used to identify factors independently associated with non-use of GP consultation for confirmation of screening results and nonresponse to the telephone follow-up survey. Results  Prevalence of glycemic abnormalities was 46.0% (95% CI = 42.7-49.2%). Among participants with impaired glycemic status (N = 417), 77.7% (95% CI = 73.7-81.7%) consulted a GP for confirmation of screening results, 12.5% (95% CI = 9.3-15.6%) did not, and 9.8% failed to respond to the follow-up survey. Factors independently associated with nonuse of GP consultation for confirmation of screening results were self-reported unwillingness to consult a GP (adjusted odds ratio [OR]: 4.86, 95% CI = 1.70-13.84), usual GP consultation frequency of less than once a year (adjusted OR: 4.13, 95% CI = 1.56-10.97), and age 18-39 years (adjusted OR: 3.09, 95% CI = 1.46-6.57). Conclusion  Home screening for glycemic abnormalities is a useful proximity health service for diabetes prevention in low socio- economic settings. Further efforts, including health literacy interventions, are needed to increase utilization of primary care.